2008
DOI: 10.1111/j.1600-079x.2007.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Function and expression of melatonin receptors on human pancreatic islets

Abstract: Melatonin is known to inhibit insulin secretion from rodent beta-cells through interactions with cell-surface MT1 and/or MT2 receptors, but the function of this hormone in human islets of Langerhans is not known. In the current study, melatonin receptor expression by human islets was examined by reverse transcription-polymerase chain reaction (RT-PCR) and the effects of exogenous melatonin on intracellular calcium ([Ca2+]i) levels and islet hormone secretion were determined by single cell microfluorimetry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
173
11
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(222 citation statements)
references
References 40 publications
19
173
11
13
Order By: Relevance
“…However, contrary to previous findings [54,55], we found that the differences between the levels of the receptor mRNAs were not as big as in human islets [56]. We also observed that the MTNR1B protein predominantly occurs in beta cells in either human or rodent islets; MTNR1A protein is found in peripherally located beta cells.…”
Section: Melatonin Receptors In Pancreatic Islets and Beta Cellscontrasting
confidence: 99%
See 4 more Smart Citations
“…However, contrary to previous findings [54,55], we found that the differences between the levels of the receptor mRNAs were not as big as in human islets [56]. We also observed that the MTNR1B protein predominantly occurs in beta cells in either human or rodent islets; MTNR1A protein is found in peripherally located beta cells.…”
Section: Melatonin Receptors In Pancreatic Islets and Beta Cellscontrasting
confidence: 99%
“…This indeed appears to be the case, as inferred from studies using the non-hydrolysable GTP analogue guanosine 5′-O-(3-thiotriphosphate) and the melatonin antagonist luzindole [51], both of which block the effects of melatonin on insulin secretion from neonatal rat islets. MTNR1A mRNA was subsequently demonstrated in INS-1 cells [52,53] and in rat [54,55] and human islets [55]. MTNR1B mRNA has also been detected in rat [54,55] and human islets [55], but at levels several-fold lower than those of MTNR1A mRNA.…”
Section: Melatonin Receptors In Pancreatic Islets and Beta Cellsmentioning
confidence: 96%
See 3 more Smart Citations